Evolution or Elimination! The Influence of Market Orientation and Innovation in Private Higher Education Institutions - Yulianti, Yulianti; Ferry Bakti (Journal of Economics and Business (JECOMBI), 2025)
Private higher education institutions face intense competition amid shifting student preferences, digital transformation, and evolving industry needs. This study investigates how market orientation and product innovation affect competitive advantage and institutional performance at ISB Atma Luhur Pangkalpinang. The research responds to the limited understanding of how market orientation, innovation, digital adaptability, and institutional image integrate to create sustainable competitive advantage. Using a quantitative approach, data were collected from 281 students out of 940 and analyzed using Partial Least Squares Structural Equation Modeling. Results show that market orientation has the strongest influence on competitive advantage (0.794), followed by product innovation (0.585) and institutional image (0.353), while digital adaptability shows no significant effect. Competitive advantage significantly affects institutional performance (0.804; R² = 0.875). The institution faces real challenges, including weak coordination across units, limited curriculum innovation, and gaps in digital readiness. This research contributes to the development of Resource Based View and Value Based Adoption Model in the context of private higher education, and offers practical insights for improving competitiveness through market oriented strategies, innovation, and institutional branding.